Influence of Stress Factors on the Development of Post-Traumatic Stress Disorder in Children: Risk Factors - Kuzmenko, Anatolii; Makarenko, Svitlana (International Journal of Statistics in Medical Research, 2024)
In the current conditions of the ongoing war in Ukraine, which began in February 2022, Ukrainian children might develop post-traumatic stress disorder (PTSD) due to stress factors caused by the conflict between Ukraine and Russian-backed separatist forces, along with the Russian military. In particular, the relationship between reduced emotional intelligence and the development of post-traumatic stress disorder in children has become more relevant. This study aimed to assess structural and cognitive changes in children with PTSD and their relationship to depression, anxiety, and event segmentation. The study methods included clinical interviews (CAPS-CA-5 scale), neuropsychological tests (short-term and long-term memory tests), self-assessment questionnaires (standardised CDI, RCADS and SCAS-Child scales), and a single-shotMRI. The results showed that patients with post-traumatic stress disorder had reduced hippocampal volume (p=0.018) and the volume of cingulate cortex isthmus (p=0.026). Diffusion in the cerebellum-hippocampal tract was reduced (p=0.014). The level of depression was positively correlated with hippocampal volume (r=0.32, p=0.021) and anxiety with the volume of cingulate cortex isthmus (r=0.26, p=0.048). These results emphasise the importance of the relationship between structural changes and levels of depression and anxiety in patients with PTSD. Prospects for further research are based on the study of the long-term effects of psychotherapeutic interventions aimed at improving cognitive function in patients with posttraumatic stress disorder.